Kandungan Acid Detergent Fiber Dan Neutral detergent Fiber Jerami Jagung fermentasi Dengan Mengunakan Jamur Trichoderma Viride Dengan Lama Inkubasi Berbeda - Natalia Usman; ellen salah (Jambura Journal of Animal Science, 2019)
The research was aimed at investingating acid detergent  fibre   neutral detergent Fiber content in corn straw fermented using Trichoderma Viride in different Incubation Time. It applied compeletey Randomizend Design consisting Of  4 treatments  and  4 repetitions,  hence, it resulted in 16 units  of  an experiment. The Treatments consisted of corn straw  withhout inoculation (control), 7%  corn straw  Fermented  with Trichoderma  viride in  1 week incubation time, 7%  corn  straw  Fermented  with Trichoderma Viride in  2 weeks incubation time, and 7% corn  straw fermented with Trichoderma Viride in 3 weeks incubation time.Analysis of variance result shows that corn straw fermented using Trichoderma  Viride in different Incubation Time gave significant inflluance toward ADF content (p0,05).  Besides ,  corn straw fermentd using Trichoderma Viride in different incubation Time gave significant influence toward NDF content(p0,05).